First records of two alien land flatworms (Tricladida, Geoplanidae) from Northeastern Italy - Dorigo, Luca; Lago, Tommaso Dal; Menchetti, Mattia; Sluys, Ronald (Zootaxa, 2020)
During a period of intense rainfall (May 2019), several specimens of land flatworms were collected from a private garden in Palazzolo dello Stella (Friuli Venezia Giulia, Udine, Italy: 45°47’40.5”N, 13°05’17.2”E). Planarians were found both in a cultivated part of the garden and in a part covered with gravel and with trees and shrubs (Pyracantha sp., Olea europaea, Pyrus communis). The animals were observed under branches, stones, tufa blocks, and pots close to a small artificial pond, but also in other parts of the garden, as well as inside buildings.